PROSES PERENCANAAN REKLAMASI PANTAI DAN PENGEMBANGAN KAWASAN STUDI KASUS PANTAI KOTA MANADO - , YUFITA FEIBE LENGKEY; , Prof. Ir. Achmad Djunaedi, MUP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The implementation of development activities may cause complex impacts. Reclamation project will change land use pattern and also increase area of the city. There is a need for a good planning process for reclamation area. This research attempts to document the process of reclamation planning and development undertaken by private sector in Manado city and factors affecting the process. The research used case study method by in depth interviews and field observations. This study takes cases on reclamation activities that carried out by four developers on the coastal area of Manado city. In general, four developers carry out reclamation planning process in the same ways which consists of the preparation phase plan, phase disposal area and the development of the region. The difference lies in the detail of each stage and the sequence of steps done. From the cross-case analysis, it showed several factors affecting the process including